Identification of VASA gene expression in in-vitro culture from Non-Obstructive Azoospermia (NOA) testicular biopsy cells: a study to unlock knowledge of male infertility - Md Isa, Muhammad Lokman; Mat Yusof, Afzan; Abdul Wahab, Azantee Yazmie; Ramli, Roszaman (2016)
The expression product of VASA gene is widely conserved germ line marker and participates in regulating the development of reproductive system and spermatogenesis in healthy man. Azoospermic is a condition which cannot produce sperm cells for reproduction activity. In Islam, seeking knowledge is an obligatory to each Muslim in order to solve problems and for a better live. Thus to unveiled the problem of azoospermic in infertile man we attempt to determine the gene expression of VASA level in testes cells of non-obstructive azoospermic (NOA) sample. Samples were taken from three NOA patients by testicular sperm extraction (TESE) to obtain testicular biopsyies. Testicular cells were isolated and cultured in supplemented knockout DMEM media. VASA gene expression was determined by reverse transcriptase polymerase chain reaction (RT-PCR) for spermatogonial marker. No VASA expression was detected in spermatogonial-like stem cells culture on day 1, 7, 14 and 21. Our finding shown VASA gene was not expressed in vitro culture spermatogenesis might be associated with the abnormal differentiation of primordial germ cells that lead to male infertility.